High Vegetable Fats Intake Is Associated with High Resting Energy Expenditure in Vegetarians - Montalcini, Tiziana (Nutrients, 2015)
It has been demonstrated that a vegetarian diet may be effective in reducing body weight, however, the underlying mechanisms are not entirely clear. We investigated whether there is a difference in resting energy expenditure between 26 vegetarians and 26 non-vegetarians and the correlation between some nutritional factors and inflammatory markers with resting energy expenditure. In this cross-sectional study, vegetarians and non-vegetarians were matched by age, body mass index and gender. All underwent instrumental examinations to assess the difference in body composition, nutrient intake and resting energy expenditure. Biochemical analyses and 12 different cytokines and growth factors were measured as an index of inflammatory state. A higher resting energy expenditure was found in vegetarians than in non-vegetarians (p = 0.008). Furthermore, a higher energy from diet, fibre, vegetable fats intake and interleukin-β (IL-1β) was found between the groups. In the univariate and multivariable analysis, resting energy expenditure was associated with vegetarian diet, free-fat mass and vegetable fats (p < 0.001; Slope in statistic (B) = 4.8; β = 0.42). After adjustment for cytokines, log(10) interleukin-10 (IL-10) still correlated with resting energy expenditure (p = 0.02). Resting energy expenditure was positively correlated with a specific component of the vegetarian’s diet, i.e., vegetable fats. Furthermore, we showed that IL-10 was positively associated with resting energy expenditure in this population.